Government of Egypt, Japan and the World Bank Jointly Address Unemployment Challenges Facing Marginalized Youth - Kaur, Iqbal (World Bank, Washington, DC, 2012)
Egypt is facing an unprecedented 'youth bulge' with approximately 60 percent of the population below the age of 30 and more unemployed youth being added every year to the labor force. However, the current youth bulge has not been fully seized as an opportunity for the country's development. Rather, it has resulted in numerous challenges, namely resource constraints to accessing education and employment opportunities for younger generations. As a result, such hardships are eroding the quality of life for families who are vulnerable to the deteriorating poverty situation and uneven growth distribution. Overall, the Egypt job readiness and job placement for marginalized youth project will create a strong impetus for youth entrepreneurship and job creation among marginalized youth and will reduce the risk of emigration to cities and abroad. The integrated monitoring and evaluation mechanisms in the design of the project will allow for a better understanding of the pros and cons of this approach throughout implementation, while providing a solid ground for post-project evaluation and potential for nation-wide replication.